A Device for Uncovering (Opening) Buried Grapevines - Yasharov, M. I.; Mirzayev, I. G.; Zulunov, Z. T.; Muqimova, Y. S. (American Journal of Biodiversity, 2025)
The article presents the design and operating principles of a device intended for uncovering soil-covered grapevine shoots in early spring in viticultural farming enterprises.